EFFECT OF PEPPERMINT AROMATHERAPY ON MENSTRUATION SCALE OF PAIN IN FAKULTAS KEDOKTERAN HANG TUAH SURABAYA STUDENTS - Rena Kartikasari (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2020)
Background : Every children will go through puberty. Puberty in girls is marked by menstruation, according to WHO 16,8%-81% of woman experience dysmenorrhea during menstruation. Pain is managed by using drugs such as analgesics, sedatives, antispasmodics. Long-term use may be ineffective and it could have bad side effects on the kidneys and liver. The culture of Indonesian people who like to use eucalyptus oil and telon oil to relieve dizziness, nausea and pain. The widespread use of essential oil aromatherapy which underlies this research.Objective : To determined the effect of aromatherapy peppermint essential oil by warm compress methods can reduce menstruation pain in Fakultas Kedokteran Universitas Hang Tuah Surabaya students.Methodology : This study uses an experimental research design. This study was carried out using a pretest-post-test control group design. Two groups consist of the intervention group (n = 21) were given peppermint essential oil by warm compresses five days before menstruation and the control group (n = 21) without any intervention. Primary data taken from filling out VAS and VMS pain scale questionnaires on the first day of menstruation after intervention.Results : Based on the results of the Mann-Whitney U non-parametric statistical test between the two groups measured using Visual Analogue Scale (VAS), a significance value of p = 0.001 (p <0.05) was obtained , H0 was rejected and H1 was accepted, a significant difference in peppermint aromatherapy on menstrual scale of pain in Fakultas Kedokteran Universitas Hang Tuah Surabaya students. The statistical test between the two groups was measured using a VMS (Visual Multidimensional Scoring System). Significant value obtained p = 0.001 then p <a, meaning that significant difference in the effect of peppermint aromatherapy on menstrual scale of pain in Fakultas Kedokteran Universitas Hang Tuah Surabaya students.Conclusion : The use of peppermint aromatherapy by warm compresses affected the reduction of the visual analogue score (VAS) and VMS (Visual Multidimensional Scoring System) on menstrual scale of pain in Fakultas Kedokteran Universitas Hang Tuah Surabaya students.Keywords : warm compress, peppermint, dysmenorrhea.